“For me, it's just a piece of freedom”—Increased empowerment through physical activity promotion among socially disadvantaged women - Sauter, Alexandra; Herbert-Maul, Annika; Abu-Omar, Karim; Thiel, Ansgar; Ziemainz, Heiko; Frahsa, Annika; Linder, Stephanie; Herrmann-Johns, Anne (Frontiers in Public Health, 2022)
Introduction Community-based participatory research (CBPR) is an effective health promotion approach for reaching socially disadvantaged groups. However, there is limited evidence on how such interventions and their effects can be reproduced across time and place. The present study examines the effects of BIG (i.e., movement as an investment in health), a long-standing German CBPR project. Since 2005, BIG has aimed to empower women in difficult life situations to increase control over their health determinants and reduce social inequalities by promoting physical activity. One of BIG's key features is its implementation in several German municipalities since 2005. This study explores (a) whether participation could change women's empowerment, and (b) how increased empowerment affects other areas of women's lives. Methods With a total of 63 interviewees (i.e., 40 participating women, 7 trainers, 3 project coordinators, and 13 stakeholders), we conducted 53 semi-structured qualitative interviews in five BIG communities between 2007 and 2011. Some interviews were conducted with two people simultaneously. The interview guide contained questions on various dimensions of empowerment (e.g., project engagement, increased self-efficacy, and developed competencies). Framework analysis was used for the analytical process. Results BIG contributed to women's empowerment in various ways, including increased self-efficacy, social network promotion, competency development, and increased motivation to change physical activity behavior. Women who took on added tasks and became more involved in project planning also strengthened their organizational empowerment. Furthermore, increased empowerment had a positive influence on the women's quality of life, family, and professional lives. Conclusion The novel findings helped in understanding the effects of a complex empowerment-based approach that promoted physical activity among women in difficult life situations. Future research should focus on the long-term effects of these programs and their transferability to other sites. Further effort is necessary in the area of public health policy.